INFLUENCE OF THE RASHBA AND DRESSELHAUS SPIN-ORBIT INTERACTIONS ON THE POLARON PROPERTIES OF A TWO-DIMENSIONAL ELECTRONS IN SEMICONDUCTOR HETEROSTRUCTURES - Vardanyan, K.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2012)
The interplay of the Rashba and Dresselhaus spin-orbit as well as the Fröhlich type electron-phonon interactions on the energy dispersion relation of the spin subbands in a two-dimensional electron gas in semiconductor polar heterostructures is studied theoretically. The Rayleigh-Schrodinger perturbation theory has been used to obtain in closed form the basic parameters of the polaron state (self-energy and effective mass) as a function of the Rashba and Dresselhaus coupling strengths.